Historiograficzne próby Lucjana Rydla - Budrewicz , Tadeusz (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
Lucjan Rydel authored a dramatic trilogy about King Sigismund II Augustus. He described the 16th century with great erudition as regards the material and political history of the period. He had studied numerous historical records as well as scholarly works. He also wrote an academic essay on Charles de Nassau. The main areas of his interest in history were texts of didactic and popular character. He wrote a monograph entitled Queen Hedwig, where he collected the themes of female rule in literature and art. He published brochures on buildings of historical interest in Krakow, Warsaw and Vilnius. He brought out A Short History of Poland and History of Poland for Everybody, both of which were written during the Great War. His ambition was to write accessible textbooks on the history of the Polish nation and Polish state with a view to boosting the patriotism of Poles. In matters of ideology, his works were leaning towards conservative views.